IMPLEMENTASI PEMBEBASAN BERSYARAT YANG DITERAPKAN DI RUMAH TAHANAN NEGARA KLAS II B RENGAT - Hilda Febriani; Dessy Artina; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Implementation of Parole is a coaching program to integrate prisoners and correctional students into community life after fulfilling specified requirements. activities to foster correctional fostered citizens based on systems, institutions and ways of fostering which constitute the final part of the criminal justice system in the criminal justice system for fostered citizens in detention centers in the IIB Rengat state already run the proper process in the penitentiary concept to foster fostered citizens to be better. Based on this understanding, the writer of this thesis formulates two problem formulations, namely: first, how is the implementation of conditional release applied in the Class II B Rengat state prison, second, what are the obstacles in the implementation of conditional release in the class II B Rengat state prisonIn the research results there are two main problems that can be concluded. First the granting of parole which has not been fulfilled according to applicable law. These two obstacles are still obstacles for prisoners who apply for paroleThis study uses an approach. This research is a sociological legal research, which is a study of the effectiveness of existing laws or research on legal identification. This means that reviewing the state of the problem in the field is related to the legal aspects that apply in the community and governing the problem. Because in this study the writer directly conducts research at the location or place of study in order to provide a complete and clear picture of the problem under study. in terms of its nature, this research is made Descriptive, namely research that describes various facts and facts contained in social life in depth.Keywords: Implementation, Parole, Detention Center